2021
DOI: 10.33448/rsd-v10i11.19252
|View full text |Cite
|
Sign up to set email alerts
|

O desmatamento da Amazônia brasileira sob o prisma da pecuária: a degradação dos recursos hídricos no contexto da região norte de Mato Grosso

Abstract: O estudo objetivou estabelecer uma relação entre o processo de desmatamento, a expansão da pecuária na Amazônia brasileira e a degradação dos corpos hídricos. A investigação seguiu uma abordagem qualitativa, com procedimentos da revisão bibliográfica e levantamento de dados de desmatamento e da produção pecuária bovina dos estados da Amazônia Legal, como forma de contextualizar o encadeamento dos projetos desenvolvimentistas desde a década de 1970. Com foco em área localizada no bioma Amazônia, no norte de Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(26 reference statements)
1
2
0
3
Order By: Relevance
“…He also points out that Brazil still has deforestation problems, which makes exporting beef with such label complex. This coincides with a study by Kohler et al (2021), who report that cattle farming was the major cause of deforestation in the Brazilian Amazon biome (north of Mato Grosso) between 1985 and 2020, with worrying cases such as Nova Bandeirantes, where 812.52 km 2 of rainforest was deforested between 2008 and 2020.…”
Section: Carne Carbono Neutralsupporting
confidence: 90%
“…He also points out that Brazil still has deforestation problems, which makes exporting beef with such label complex. This coincides with a study by Kohler et al (2021), who report that cattle farming was the major cause of deforestation in the Brazilian Amazon biome (north of Mato Grosso) between 1985 and 2020, with worrying cases such as Nova Bandeirantes, where 812.52 km 2 of rainforest was deforested between 2008 and 2020.…”
Section: Carne Carbono Neutralsupporting
confidence: 90%
“…Illegal activities such as indiscriminate tree cutting and unauthorized exploitation of natural resources compromise the integrity of these protected areas, as well as pose a direct threat to the biological diversity of the Amazon. Such illegal practices also undermine conservation and sustainability efforts (Barroso & Mello, 2020;Kohler et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that deforestation significantly reduces precipitation and ET (Costa and Foley, 2000;Nóbrega, 2014;Santos et al, 2017;Saddique et al, 2020). Other works carried out in the Amazon Forest highlight the impact of vegetation cover changes on the water balance (Pongratz et al, 2006;Hayhoe et al, 2011;Griffiths et al, 2018;Cabral Júnior et al, 2022) and actual ET (Souza et al, 2019;Kohler et al, 2021;Paiva et al, 2023).…”
Section: Introductionmentioning
confidence: 99%